2014
DOI: 10.1089/ars.2013.5653
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Skin Extracellular Matrix Induced by UV Exposure

Abstract: Both topical antioxidants and inhibitors of detrimental cell signaling may be effective in abrogating the effects of specific UVR-mediated protein degradation in the dermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 167 publications
4
131
0
1
Order By: Relevance
“…45 Even with minimal photo-aging one can appreciate loss of fibrillin-rich microfibrils in the dermalepidermal junction -an early marker of photoaging. 46,47, 48 There is general agreement that epidermal cell turnover halves between the third and seventh decades of life, 49,50 and this concurs with the observed deterioration in wound healing capacity in old age. 51 …”
Section: Epidermismentioning
confidence: 73%
“…45 Even with minimal photo-aging one can appreciate loss of fibrillin-rich microfibrils in the dermalepidermal junction -an early marker of photoaging. 46,47, 48 There is general agreement that epidermal cell turnover halves between the third and seventh decades of life, 49,50 and this concurs with the observed deterioration in wound healing capacity in old age. 51 …”
Section: Epidermismentioning
confidence: 73%
“…Besides direct damage to macromolecules such as nucleotides (i.e., DNA and RNA), lipids, and proteins, both UVA and UVB exert effects through triggering oxidative stress [1,30]. In HaCaT cells (70-80% confluence) we observed that 160 kJ/m 2 of UVA irradiation caused a cell viability loss of 22%.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that solar ultraviolet (UV) irradiation of human skin leads to photoaging, immunosuppression, inflammation, and ultimately carcinogenesis [1,2,3]. Ultraviolet A (UVA) comprises the largest portion (>95%) of the solar UV radiations reaching the biosphere, and is also a predominant source to trigger oxidative stress in human skin [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is induced by reactive oxygen species (ROS) and reactive nitrogen species (RNS), which are produced in the normal cellular redox process [3]. UV exposure enhances ROS/RNS production [4,5,6], and the free radicals cause skin damage including apoptosis by interacting with DNAs, RNAs, and proteins [7]. Several lines of evidence have pointed to the implication of mitogen-activated protein kinase, aryl hydrocarbon receptor, transcription factors, such as nuclear factor-κB and nuclear factor erythroid 2-related factor 2, or matrix metalloproteinase in the degradation of dermal connective tissue following oxidative stress-induced skin damage [8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%